Diamond, Mortensen y Pissarides: Premios Nobel de Economía 2010 e implicancias para la economía peruana - Roca Garay, Richard (2010)
This article presents a summary of the contributions of the new Nobel Prizes in Economics, the professors Diamond, Mortensen and Pissarides and their main publications. In addition it presents a reflection on the principal implications for the Peruvian economy.